Does transformational leadership encourage organizational commitment? - Roby Sambung; Ricky Kristiawan; Olivia Winda Ony Panjaitan (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2021)
This study aims to determine whether job satisfaction mediates the relationship between transformational leadership and the organizational commitment of civil servants. A structural equation modelling approach was used to test the collected data with a sample of 51 respondents. The results show that job satisfaction can mediate the relationship between transformational leadership and organizational commitment.